ANALISIS PRODUKSI USAHATANI KAKAO DI DESA MASARI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Asrar, Saharia Kassa, Rustam Abd. Rauf, Irsad (AGROTEKBIS, 2015)
This study aimed to determine the effect of  plant number, fertilizers, pesticides, and labor on the production of cacao farming in Masari Village, South Parigi Sub District, Parigi Moutong District. Determination of respondents used a simple random technique.  The analysis tool used was the Cobb-Douglas production function. The analysis shows that the coefficient of determination (R2) was 0.856 indicating that the dependent variable of the cocoa farm production was 85.6% affected by the independent variables tested by the reasearchers, while the remaining 14.4% was affected by other variables outside the model.  The result of F-test showed that number of producing plants (X1), fertilizers (X2), pesticides (X3) and labor (X4) simultaneously had significant effect on the cacao production..  The results of t-test also suggested that individually all independent variables significantly affected the production of the cacao farming in Masari Village, South Parigi Sub District, Parigi Moutong District.